Amorphous Fe(OH)3 Passivating CeO2 Nanorods: A Noble‐Metal‐Free Photocatalyst for Water Oxidation. Issue 16 (22nd July 2021) - Feng, Ting; Ding, Jing; Li, Haiyan; Wang, Wei; Dong, Bohua; Cao, Lixin
Abstract: Noble‐metal‐free composites with good photocatalytic property are of great interest. Here, CeO2 nanorods composites loaded with amorphous Fe(OH)3 cocatalyst were designed and prepared via a secondary water bath at 100 °C. The as‐synthesized CeO2 /amorphous Fe(OH)3 composites exhibited superior light photocatalytic activities compared to pure CeO2, especially the sample with a loading time of 60 min. The photocatalytic oxygen generation rate could reach to 357.2 μmol h −1  g −1, and the average apparent quantum yield (AQY) was 24.67 %, which was a 5.5‐fold increase compared to the CeO2 sample. The improvement of photocatalytic performance could be ascribed to three main reasons: First, loading the amorphous Fe(OH)3 enlarged the specific surface area and passivated the surface of the pristine CeO2 . Second, the amorphous Fe(OH)3, which acted as a cocatalyst, provided many active sites, and reduced the reaction activation energy. Thirdly, the maximum interface with intimate contact between CeO2 and amorphous Fe(OH)3 cocatalyst accelerated the photogenerated charge separation efficiency and thus improved the photocatalytic performance of CeO2 in photocatalytic water oxidation. Abstract : In hot water : CeO2 /A−Fe(OH)3 composites synthesized by a secondary water bath at 100 °C exhibit superior photocatalytic activity. A−Fe(OH)3 increases specific surface area, passivates the surface of CeO2, and reduces the activation energy of water oxidation. This work provides a new insight into exploring amorphous cocatalysts to enhance photocatalytic O2 evolution activity and augment the possibility of overall water splitting based on CeO2 .